2015
DOI: 10.1590/s0102-053620150000400013
|View full text |Cite
|
Sign up to set email alerts
|

Use of organic amendments in the management of root-knot nematode in lettuce

Abstract: Root-knot nematodes, Meloidogyne spp., are among the most important parasites of the lettuce crop. Managing these organisms is difficult due to limitations in genetic (use of resistant cultivars) and chemical control. Thus, new practices should be sought to reduce their reproduction. The present study aimed to evaluate the application of organic amendments in the control of Meloidogyne incognita in lettuce. At first, tomato plants were inoculated to establish an initial population in the soil. After 60 days, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…The beneficial effect of bokashi on lettuce growth was previously reported when 20 g of the product were applied per pot with 2 L of soil, with increases in doses from 0.66 to 26.15 g and 2.52 to 26.71 g, in experiments conducted in different periods (Dias-Arieira et al, 2015). In addition to lettuce, bokashi promoted increase in the vegetative growth of tomato plant when used in the substrate composition for seedlings (Zandron et al, 2003) or in planting (Roldi et al, 2013).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The beneficial effect of bokashi on lettuce growth was previously reported when 20 g of the product were applied per pot with 2 L of soil, with increases in doses from 0.66 to 26.15 g and 2.52 to 26.71 g, in experiments conducted in different periods (Dias-Arieira et al, 2015). In addition to lettuce, bokashi promoted increase in the vegetative growth of tomato plant when used in the substrate composition for seedlings (Zandron et al, 2003) or in planting (Roldi et al, 2013).…”
Section: Resultsmentioning
confidence: 54%
“…Above these doses, there was increase of nematodes, possibly due to toxic effect on the plants discussed previously. Recently, it was reported that the application of 20 g of bokashi/pot containing 2 L of soil reduced the M. incognita reproduction in lettuce in two experiments conducted in different periods (Dias-Arieira et al, 2015). In tomato, the reproduction of M. incognita was also reduced with the use of 20 g/plant: the number of eggs+J2/g decreased from 5857.8 to 251.4 in treated and non-treated plants, respectively, and the presence of castor bean cake being considered one of the likely factors that act on nematodes (Roldi et al, 2013), since the efficiency of castor bean cake in the control of plant-parasitic nematodes was demonstrated in several studies involving different pathosystems (Dutra et al, 2006;Lopes et al, 2009;Roldi et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, adding organic matter to the soil is one of the most efficient methods for the sustainable control of nematodes affecting vegetables; different organic wastes showed nematode management potential (Lopes et al, 2009;Nazareno et al, 2010;Roldi et al, 2013;Dias-Arieira et al, 2015). The organic matter addition also presents other benefits such as natural enemy population increase and improvements in the physical and chemical properties of the soil, including base saturation, porosity and water conductivity, which allow plants to develop better, as well as to become more resistant to these pathogens (McSorley & Gallaher, 1995;Oka, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Crambe (Crambe abyssinica Hochst) is another crop whose cake presents nematode control potential (Dias-Arieira et al, 2015;Tavares-Silva et al, 2015). The species is an oleaginous brassica, which presents oil conversion efficiency; the crambe oil is characterized by its high erucic acid content-a long-chain fatty acid used to make chemical products (Erikson & Bassin, 1990;Pitol et al, 2010).…”
Section: Introductionmentioning
confidence: 99%